Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

PPARγ activation regulates lipid droplet formation and lactate production in rat Sertoli cells - A. Gorga; G. M. Rindone; M. Regueira; E. H. Pellizzari; M. C. Camberos; S. B. Cigorraga; M. F. Riera; M. N. Galardo; S. B. Meroni (Cell and Tissue Research, 2017)

Zn- vs Bi-based oxides for o-toluidine photocatalytic treatment under solar light - E. Pargoletti; S. Mostoni; G. Rassu; V. Pifferi; D. Meroni; L. Falciola; E. Davoli; M. Marelli; G. Cappelletti (Environmental Science and Pollution Research, 2017)

Healthy and tumoral tissue resistivity in wild-type and sparc–/– animal models - D. Meroni; G. Mauri; D. Bovio; A. M. Bianchi; C. Chiodoni; M. P. Colombo; E. Meroni; A. Aliverti (Medical & Biological Engineering & Computing, 2016)

The role of the urban system dysfunction in the assessment of seismic risk in the Mt. Etna area (Italy) - F. Meroni; G. Zonno; R. Azzaro; S. D’Amico; T. Tuvè; C. S. Oliveira; M. A. Ferreira; F. Mota de Sá; C. Brambilla; R. Rotondi; E. Varini (Bulletin of Earthquake Engineering, 2016)

Remote sensing of larch phenological cycle and analysis of relationships with climate in the Alpine region - L. BUSETTO; R. COLOMBO; M. MIGLIAVACCA; E. CREMONESE; M. MERONI; M. GALVAGNO; M. ROSSINI; C. SINISCALCO; U. MORRA DI CELLA; E. PARI (Global Change Biology, 2010)
This research aims at developing a remote sensing technique for monitoring the interannual variability of the European larch phenological cycle in the Alpine region of Aosta Valley (Northern Italy) and to evaluate its relationships with climatic factors. Phenological field observations were conducted in eight test sites from 2005 to 2007 to determine the dates of completion of different phenological phases. MODerate Resolution Imaging Spectrometer (MODIS) 250 m 16‐days normalized difference vegetation index (NDVI) time series were fitted with double logistic curves and the dates corresponding to different features of the curves were determined. Comparison with field data showed that the features of the fitted NDVI curve that allowed the best estimate of the start and end of the growing season were the zeroes of its third derivative (MAE of 6 and 4 days, respectively). The start and end of season were also estimated with the spring warming (SW) and growing season index (GSI) phenological models. MODIS start and end of season dates generally agreed with those obtained by the SW and GSI climate‐driven phenological models. However, phenological models provided erroneous results when applied in years with anomalous meteorological conditions. The relationships between interannual variability of the larch phenological cycle and climate were investigated by comparing the mean start and end of season yearly anomalies with air temperature anomalies. A strong linear relationship ( R 2 =0.91) was found between mean spring temperatures and mean start of season dates, with an increase of 1 °C in mean spring temperature leading to a 7‐day anticipation of mean larch bud‐burst date. Leaf coloring dates were found to be best related with mean September temperature ( R 2 =0.77), but with higher spring temperatures appearing to lead to earlier leaf coloring.

European larch phenology in the Alps: can we grasp the role of ecological factors by combining field observations and inverse modelling? - M. Migliavacca; E. Cremonese; R. Colombo; L. Busetto; M. Galvagno; L. Ganis; M. Meroni; E. Pari; M. Rossini; C. Siniscalco; U. Morra di Cella (International Journal of Biometeorology, 2008)

Persistent parvovirus B19-induced anemia in an HIV-infected patient under HAART. Case report and review of literature - P. Morelli; G. Bestetti; E. Longhi; C. Parravicini; M. Corbellino; L. Meroni (European Journal of Clinical Microbiology & Infectious Diseases, 2007)

Analysis of Candidate Genes at the IBGC1 Locus Associated with Idiopathic Basal Ganglia Calcification (“Fahr” Disease’) - J. R. M. Oliveira; M. J. Sobrido; E. Spiteri; S. Hopfer; G. Meroni; E. Petek; M. Baquero; D. H. Geschwind (Journal of Molecular Neuroscience, 2007)

Declining Incidence of AIDS and Increasing Prevalence of AIDS Presenters Among AIDS Patients in Italy - B. Castelnuovo; E. Chiesa; S. Rusconi; F. Adorni; M. Bongiovanni; S. Melzi; P. Cicconi; F. Tordato; L. Meroni; T. Bini; A. d’Arminio Monforte (European Journal of Clinical Microbiology & Infectious Diseases, 2003)